Analisis Pemenuhan Hak Konstitusional Warga Negara dalam Pelayanan Publik: Studi Kasus Akun Tiktok Sesilia Yovani Saragih - Hadriyani, Siti; Simarmata, Eka Santi; Panjaitan, Gita Jesica; Nugraha, Gusnadi; Alfiandra, Muhammad Diki; Ardika, Raja; Hasibuan, Hamdi Abdullah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research analyzes the gap between the guarantee of constitutional rights in public services and the reality of their implementation in the field, using a case study of Sesilia Yovani Saragih's viral TikTok video about her experience in obtaining an electronic ID card. The video exposes how a supposedly simple administrative procedure turns into a bureaucratic process that is complicated, non-transparent, and contains illegal levies. Using a qualitative approach with a case study method, this research integrates juridical analysis of the 1945 Constitution, Law No. 25 of 2009, and Law No. 24 of 2013, as well as thematic analysis of social media content and public response. The findings show that there are still violations of citizens' rights in the form of inequality of access, administrative discrimination, and low quality of public services. The root of the problem is identified in structural, cultural, and weak law enforcement factors. The research recommends comprehensive reform through the preparation of clear standard operating procedures, strengthening the supervisory system, increasing service transparency, strict law enforcement against corrupt practices, and implementing digital transformation centered on the needs of the community. These efforts are expected to realize the fulfillment of citizens' constitutional rights in public services optimally.